Pengembangan Modul Pembelajaran Berbasis Game untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VIII - Nabila Lubis, Putri; Lisa Dwi Afri; Rusi Ulfa Hasanah; Siti Maysarah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to develop a game-based learning module and examine its validity, practicality, and effectiveness in improving the mathematical problem-solving abilities of eighth-grade students. The background of this research is based on the low performance of students in solving problem-solving tasks, as well as the limited availability of learning media that support independent study. The module development process employed the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The trial subjects were 19 eighth-grade students. Research instruments included validation sheets, pre-tests, post-tests, and teacher and student response questionnaires. The validation results indicated that the module is highly valid, with scores of 82.5% from the content expert and 87.5% from the media expert. The module was also found to be highly practical, based on positive responses from the teacher (100%) and students (96.14%). Effectiveness testing using the N-Gain analysis showed an average score of 0.68, which falls into the medium category. These findings suggest that the developed game-based learning module is feasible for classroom use and effective in supporting the improvement of students’ mathematical problem-solving skills.